Serum thyroid-stimulating hormone concentration and morbidity from cardiovascular disease and fractures in patients on long-term thyroxine therapy - Flynn, Robert W; Bonellie, Sandra R; Jung, Roland T; MacDonald, Thomas M; Morris, Andrew D; Leese, Graham P (The journal of clinical endocrinology and metabolism, 2010)
For patients on T(4) replacement, the dose is guided by serum TSH concentrations, but some patients request higher doses due to adverse symptoms. The aim of the study was to determine the safety of patients having a low but not suppressed serum TSH when receiving long-term T(4) replacement. We conducted an observational cohort study, using data linkage from regional datasets between 1993 and 2001. A population-based study of all patients in Tayside, Scotland, was performed. All patients taking T(4) replacement therapy (n = 17,684) were included. Fatal and nonfatal endpoints were considered for cardiovascular disease, dysrhythmias, and fractures. Patients were categorized as having a suppressed TSH (<or=0.03 mU/liter), low TSH (0.04-0.4 mU/liter), normal TSH (0.4-4.0 mU/liter), or raised TSH (>4.0 mU/liter). Cardiovascular disease, dysrhythmias, and fractures were increased in patients with a high TSH: adjusted hazards ratio, 1.95 (1.73-2.21), 1.80 (1.33-2.44), and 1.83 (1.41-2.37), respectively; and patients with a suppressed TSH: 1.37 (1.17-1.60), 1.6 (1.10-2.33), and 2.02 (1.55-2.62), respectively, when compared to patients with a TSH in the laboratory reference range. Patients with a low TSH did not have an increased risk of any of these outcomes [hazards ratio: 1.1 (0.99-1.123), 1.13 (0.88-1.47), and 1.13 (0.92-1.39), respectively]. Patients with a high or suppressed TSH had an increased risk of cardiovascular disease, dysrhythmias, and fractures, but patients with a low but unsuppressed TSH did not. It may be safe for patients treated with T(4) to have a low but not suppressed serum TSH concentration.